2006
DOI: 10.2215/cjn.01351005
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular versus Surgical Preemptive Repair of Forearm Arteriovenous Fistula Juxta-Anastomotic Stenosis

Abstract: Surgery is the traditional treatment for juxta-anastomotic stenoses in forearm arteriovenous fistulas (AVF), but percutaneous transluminal angioplasty (PTA) is a suitable alternative. No prospective comparative trials between the two have been reported to date, however. A retrospective analysis of prospectively, concurrently collected data was performed to compare the outcome and cost of surgery and PTA in the preemptive repair of juxta-anastomotic stenosis in lower forearm AVF. Sixty-four AVF with >50% venous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
61
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 32 publications
6
61
0
4
Order By: Relevance
“…Unfortunately, little is known about the prognostic factors that directly influence the FEI. Indeed, most published series have evaluated prognostic factors influencing the PP rate (ie, delay of first restenosis) (1,3,4,6,16,17) or the APP/SP rate (ie, long-term patency regardless of the number of interventions) (3,4,6,12,13). To our knowledge, only one study (4) assessed the influence of AVF location on FEI, and it found a significantly higher rate of interventions in brachiocephalic (0.77/y) than in radiocephalic (0.41/y) AVFs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, little is known about the prognostic factors that directly influence the FEI. Indeed, most published series have evaluated prognostic factors influencing the PP rate (ie, delay of first restenosis) (1,3,4,6,16,17) or the APP/SP rate (ie, long-term patency regardless of the number of interventions) (3,4,6,12,13). To our knowledge, only one study (4) assessed the influence of AVF location on FEI, and it found a significantly higher rate of interventions in brachiocephalic (0.77/y) than in radiocephalic (0.41/y) AVFs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, little is known about the prognostic factors that could influence the outcome of endovascular procedures in the specific group of JASs of forearm stenoses. One study could not identify any significant prognostic factor (16), whereas a stenosis at the anastomotic site itself and smoking significantly increased the risk of restenosis in another (17). Therefore, we undertook the present study to assess the long-term outcome of endovascular treatment of JASs in forearm AVFs, and to identify potential prognostic factors of failure that could orient patients toward first-line surgical management.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Venous problems have been regarded as the principal culprits for access dysfunction for a long time, with much less importance given to inflow problems which had an incidence of 0% to 4% (12). Although, in the last few years, inflow stenoses have been shown to be present in approximately 25% to 50% of the dysfunctional access (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Both radiocephalic and brachiocephalic fistulas commonly fail because of lesions located within the perianastomotic region; however, more proximal stenoses can also occur in both cases, especially in the case of brachiocephalic fistulas (cephalic arch stenosis) (27).…”
Section: Discussionmentioning
confidence: 99%
“…36 Restenosis rates were significantly higher after angioplasty, but overall costs of treatment were similar. Nonmatured fistulas are rescued by angioplasty of stenoses or occlusions, ligation of accessory veins, or both.…”
Section: Nonmaturation Of Av Fistulasmentioning
confidence: 96%